AN ANALYSIS OF THE LEADERSHIP VALUES, MESSAGES AND TYPES IN THE MOVIE “FURY” BY DAVID AYER - Iradatul Akbar; Iwan Jazadi (GLOBAL: Education Language and Humanity Journal, 2024)
This research focused on analyzing the leadership in the movie “Fury”. This research aimed to describe the leadership values, messages, and types in the movie. This research applied descriptive qualitative method. The object of this research was the movie “Fury” by David Ayer. The data were analyzed using content or document analysis. The findings of this research include the following. First, the leadership values in the movie “Fury” include being physically strong, purposeful, enthusiastic, friendly, affectionate, consistent, technically skilled, decisive, intelligent, and faithful. Second, leadership messages in the movie are performing orders, sacrifice, facing any problems, firmness, striving to the end and no giving up in any circumstances. Third, the type of leadership contained in the movie is charismatic.